Successful pregnancy after chemotherapy and surgery for an anterior abdominal wall desmoid tumor - Waghmare, Chaitali Manohar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Desmoid tumors are said to be hormone dependant tumors and are common during or after pregnancy. This is a case of a young lady who successfully delivered after chemotherapy and surgery for an anterior abdominal wall desmoid tumor. This shows subsequent pregnancy is not a contraindication after treatment of desmoid tumor and there is no increased risk of local recurrence or new disease after pregnancy.